Orientation-dependent hardness and nanoindentation-induced deformation mechanisms of WC crystals. (15th January 2015) - Csanádi, Tamás; Bl'anda, Marek; Chinh, Nguyen Q.; Hvizdoš, Pavol; Dusza, Ján
Abstract: The orientation dependence of hardness and nanoindentation-induced deformation mechanisms of differently orientated tungsten carbide (WC) grains in WC–Co hardmetal were studied. Electron backscatter diffraction, atomic force microscopy and scanning electron microscopy investigations were performed to determine the grain orientation, and to study the surface morphology and the resulting deformation fields around the indents. The hardness of the differently orientated WC grains showed significant angle dependence from the basal towards the prismatic directions, but there was only a slight change in hardness between the two types of prismatic orientations ( ( 1 0 1 ¯ 0 ) and ( 2 1 ¯ 1 ¯ 0 ) ). Sink-in and pile-up effects, together with highly deformed regions and dislocation steps, were revealed around the imprints in the case of basal and prismatic orientations, respectively. A theoretical model is proposed in which the critical force for slip activation is determined as a function of orientation, based on the possible slip systems of WC. The predictions of the present model concerning the measured hardness values and the deformation field around the indents together with the sink-in effect are in good agreement with the experimental results.